PENYIDIKAN TINDAK PIDANA PENISTAAN AGAMA MELALUI MEDIA INTERNET OLEH RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Suri, Aidil Fitri; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cyber crime is one of the dark sides of technological advances that have a very wide negative impact on all areas of modern life today. Crime which is a crime of cyber crime is Illegal contents, that is evil by entering data or information to internet about something that is not true, unethical, and is considered to violate law or disturb public order. Based on data that writer get at Directorate of Criminal Investigation Special Police Region Riau, there is one form of crime cyber crime namely the Crime of Penusaan Religion through Internet Media, the crime of defamation of religion through internet media regulated in Article 28 paragraph (2) of Law Number 19 year 2016 about the change of Law Number 11 Year 2008 on Information and Electronic Transactions which reads: "Every person intentionally and without right to disseminate information aimed at generating a sense of hatred or hostility of certain individuals and / or community groups based on ethnicity, religion, race and intergroup (SARA)."That sanction a crime of blasphemy through his internet media tour in Article 45A paragraph (2) of Law Number 19 Year 2016 concerning the amendment to Law Number 11 Year 2008 regarding Information and Electronic Transactions reads: Any person who knowingly and without right to disseminate information intended to incite a sense of hatred or hostility certain individuals and / or community groups based on ethnicity, religion, race, and intergroup (SARA) as referred to in Article 28 paragraph (2) shall be punished with imprisonment for a maximum of 6 (six) years and / or a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah).The purpose to be discussed in this thesis is to know how the investigation of the criminal act of defamation of religion through internet media conducted by Special Criminal Investigation Directorate of Riau Regional Police, and how the role of an organization of Islam in a settlement of criminal mishandling case and some obstacles that must faced in seeking law enforcement against a crime of Information and Electronic Transactions and efforts to overcome these obstaclesKeyword: Investigation-Ethnicity,Religion,Race And Intergroup (SARA)-Cyber Crime